The Existence Of Islamic Education and Ideological Reinforcements. - Abdul Aziz Bin Mustamin; Darmawati Darmawati (At-Ta'lim : Media Informasi Pendidikan Islam, 2020)
Abstract: The Existence of Islamic Education and Ideological Reinforcements The dynamics of the long history of Islamic schools, either directly or indirectly, greatly influence the flow of thought patterns in Islamic education. There are Islamic thoughts characterized by kalam, fiqh, and Sufism. The kalam-style Islamic school, for example, has been able to ensure that its educational thinking tends to be rational and philosophical in seeing social reality and phenomena. We can see this in the religious and rational style of Islamic education represented by the Ikhwan al-Shafa. Likewise, with the Islamic school which is characterized by fiqh and Sufism, its influence on Islamic education can be seen in the conservative and pragmatic stream of Islamic education. This type of educational thinking was represented by Al-Ghazali and Ibn Khaldun, and its influence can now be felt in Islamic boarding schools and madrasas in the country. This research uses the literature study method to synthesize new thoughts from the phenomena that occur in Islamic education in Indonesia. The results of this study are that Islamic education in Indonesia has a major role in the philosophical approach of implementing religious life in schools and communities.Abstrak: Eksistensi Pendidikan Islam dan Penguatan Ideologis Dinamika sejarah panjang pesantren, baik secara langsung maupun tidak langsung, sangat mempengaruhi aliran pola pikir dalam pendidikan Islam. Ada pemikiran Islam yang bercirikan kalam, fiqh dan tasawuf. Pesantren ala kalam, misalnya, telah mampu memastikan bahwa pemikiran pendidikannya cenderung rasional dan filosofis dalam melihat realitas dan fenomena sosial. Kita bisa melihat ini dalam gaya pendidikan Islam religius dan rasional yang diwakili oleh Ikhwan al-Shafa. Begitu pula dengan pesantren yang bercirikan fikih dan tasawuf, pengaruhnya terhadap pendidikan Islam dapat dilihat pada aliran pendidikan Islam yang konservatif dan pragmatis. Jenis pemikiran pendidikan ini diwakili oleh Al-Ghazali dan Ibn Khaldun, dan pengaruhnya sekarang dapat dirasakan di pesantren dan madrasah di tanah air. Penelitian ini menggunakan metode studi literatur untuk mensintesis pemikiran baru dari fenomena yang terjadi dalam pendidikan Islam di Indonesia. Hasil dari penelitian ini adalah bahwa pendidikan Islam di Indonesia memiliki peran utama dalam pendekatan filosofis dalam penyelenggaraan kehidupan beragama di sekolah dan masyarakat.